77 Implantable cardioverter-defibrillator in pregnancy- do we know what to do?. (5th June 2017) - Demetriades, Polyvios; Chong, Hsu; Thorne, Sara; Marshall, Howard; DeBono, Joseph; Morris, Katie; Lucy, Hudsmith
Abstract : Introduction: The number of women of reproductive age with an implantable cardioverter-defibrillator (ICD) is increasing, many with Adult Congenital Heart Disease or inherited cardiomyopathy. Safe management of these patients during pregnancy, labour and delivery is paramount. Guidelines exist for ICD management in non-obstetric surgical procedures but there is little information for outcomes in pregnancy or management of ICDs in elective and emergency obstetric surgery. AIMS: To investigate knowledge of health care workers about the management of ICDs in pregnancy, prior to drafting new guidelines. Methods: Paper and electronic copies of the focused questionnaire were distributed to healthcare workers within the departments of cardiology, anaesthetics and obstetrics at a large quaternary cardiothoracic centre and separate but co-located tertiary obstetric unit Results: 87 responses were returned (58% Obstetrics, 33% Cardiology, 9% Anaesthetics). Most respondents were trainees (37%) followed by consultants (28%), midwives (20%), physiologists (11%) and others (4%). Most (59%) of the cardiology team had treated a pregnant woman with an ICD. Overall, only 30% of respondents were confident about inactivating an ICD in an emergency using a magnet (4% obstetrics, 79% cardiology, 12% anaesthetists) and only 20% were aware of the magnet's location in delivery suite. Most respondents (53%) were unsure about when to inactivate an ICD (70% of obstetric team, 32% cardiologists, 50% cardiac physiologists) and whether to inactivate in an emergency Caesarian section. When seeking guidance, most respondents (64%) would contact the cardiology team, 46% the cardiac physiologists and 13% the anaesthetist. However, 88% of cardiologists said they would contact the physiologist whereas most (83%) physiologists would contact the cardiologist. Conclusions: Knowledge of ICD use in pregnancy was poor amongst those surveyed. It is of concern that most obstetricians would call the cardiology SpR or physiologists, many of whom are not confident in the emergency management of ICDs in pregnancy. We plan to introduce guidelines, signposting stickers on obstetric notes and training involving the cardiology, obstetrics and anaesthetic departments regarding its use and then re-assess knowledge to optimise patient safety. There is an urgent need for coordinated national guidelines and registries on the management of implantable cardiac devices in pregnancy.